Meat Products of the Population of the Jizak Oak and their Relatives - Sharipovich, Eshmuhamatov Akhror; Faxriddinovich, Musinov Najmiddin (European Journal of Life Safety and Stability (2660-9630), 2022)
This article covers the role of meat products in the daily life of the livestock population of the Jizzakh oasis and methods of its preparation, as well as historical information about the customs associated with these dishes, as well as ethnographic field research.